Influência da laminação a quente nas propriedades termodinâmicas, microestruturais e mecânicas de uma liga CuAlBeNbNi - Pedrosa, Marcus Túlio Magalhães Andrade (2021)
Semi-finished products, on an industrial scale, of shape memory alloys can be obtained through the hot rolling process. This work aimed to study the influence of hot rolling on the thermodynamics, microstructural and mechanical properties of a CuAlBeNbNi alloy. The influence of the percentage of thickness reduction and the sample removal region on these properties was evaluated. A reduction in the percentage of the austenite phase was observed due to the reduction in thickness for samples from the central region and an increase in the percentage of this phase for samples from the superficial region. An abnormal growth of the grains was verified for the samples of the central and superficial region for the percentages of thickness reduction of 50% and 75%. The transformation temperatures were more sensitive to the region of sample removal than to the percentage of thickness reduction. The modulus of elasticity, estimated from the ultra-microhardness tests, for samples from the superficial region were lower than those from the central region. This behavior is associated with a greater presence of the martensite phase in the superficial region, which is explained by the oxidation of the surface and consequently a compositional modification of the aluminum and / or beryllium contents. In addition, the influence of the indentation load on the mechanical properties of the samples of the superficial and central regions was evaluated. A reduction in the module and hardness was verified with the increase of the indentation load. The residual and maximum depths increased with increasing indentation load. This evolution of the mechanical properties with the indentation load is related to the demaclation mechanisms that occurred in the loading phase for samples with a predominance of the martensite phase and the stabilization of the martensite induced as a result of defects generated during the deformation that inhibit the movement of the martensite interfaces -austenite.